2017
DOI: 10.1186/s12893-017-0317-8
|View full text |Cite
|
Sign up to set email alerts
|

Using patient data to optimize an expert-based guideline on convalescence recommendations after gynecological surgery: a prospective cohort study

Abstract: BackgroundConvalescence advice is often based on tradition and anecdote from health care providers, rather than being based on experiences from patients themselves. The aim of this study was to analyse recovery in terms of resumption of various daily activities including work, following different laparoscopic and abdominal surgery in order to optimize an expert-based guideline on convalescence recommendations.MethodsThis is a prospective cohort study conducted in nine general and one university hospital in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 40 publications
1
14
0
2
Order By: Relevance
“…Vonk Noordegraaf et al found that increasingly levels of invasiveness of surgical procedures were associated with an increased risk of longer times off work [20]. Another study has shown that the time until patients can resume everyday activities becomes longer when the invasiveness of the procedure increases [24]. Similarly, the patients in our study who underwent the most invasive procedures were off work longest.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Vonk Noordegraaf et al found that increasingly levels of invasiveness of surgical procedures were associated with an increased risk of longer times off work [20]. Another study has shown that the time until patients can resume everyday activities becomes longer when the invasiveness of the procedure increases [24]. Similarly, the patients in our study who underwent the most invasive procedures were off work longest.…”
Section: Discussionsupporting
confidence: 57%
“…Sometimes sick leave is extended beyond the recommended period at the request of the affected women [10]. In their study, Bouwsma et al found that both the period until patients returned to work and the period until various physical activities were resumed were longer than the period recommended by experts [24]. Moreover, patient expectations of having a long period of sick leave can lead to an extended sick leave [20].…”
Section: Discussionmentioning
confidence: 99%
“…If convalescence was discussed in the consultation, the problems were expected to be understated. These perceptions are supported by a study comparing information provided by gynecologists regarding expected recovery after gynecological surgery with actual return to various activities of daily living (18). Insu cient knowledge while waiting for elective hysterectomy could lead to fear both regarding the indication for surgery as well as the surgery itself, although alleviated if there was a trust in the treating gynecologist.…”
Section: Discussionmentioning
confidence: 99%
“…If convalescence was discussed in the consultation, the problems were expected to be understated. These perceptions are supported by a study comparing information provided by gynecologists regarding expected recovery after gynecological surgery with actual return to various activities of daily living [19]. Experiences of failed medical treatment prior to being accepted for hysterectomy, which is common due to the standard of exhausting the pharmacological options before surgery, would also influence the trust of the information given.…”
Section: Discussionmentioning
confidence: 99%